Level of jaw mineralization in patients with estrogen imbalance according to computed tomography data - Барило, Олександр Семенович; Агафонов, Кирило В’ячеславович; Фурман, Руслан Леонідович (Actual Dentistry, 2019)
Objective. To increase the effectiveness of the prevention of caries and non-carious dental lesions in patients with estrogen imbalance. Materials and methods. To quantify the density of the bone tissue of the jaws by the method of computed tomography of the structures, an X-ray attenuation scale, called the Hounsfield scale, was used. A Planmeca ProMax 3Ds cone beam computed tomograph was used. To process the results, Planmeca Romexis® software was used. To confirm the imbalance of estrogen, all patients underwent a study on the level of estrogen (estradiol) in the body. For an indirect study of the degree of osteoporosis (bone destruction), we determined the level of serum acid phosphatase. For the study, 3 groups of patients were selected: a comparison group (20 patients) – patients who had not received additional treatment, main group 1 (20 patients) – patients who underwent general therapy with complex calcium preparations, main group 2 (20 patients) – patients who underwent general therapy with complex preparations of calcium and aminobisphosphonates. Results. At the beginning of the study, all groups showed significant demineralization of bone tissue. After 6 months in thecomparison group, the Hounsfield index remained almost unchanged and amounted to 1497±63, which indicates the absence of dynamics in this group. In the main group 1, the Hounsfield index was 1571±44, which is only 5.28% better than the initial result. In the main group 2, the Hounsfield index was 1701±48, which is 13.05% more than the initial result. At the beginning of the study, all groups showed a significant increase in the level of acid phosphatase. So, the indicators in the comparison group, the main group 1, and in the main group 2 were 6.75±0.29, 6.81±0.56, 6.79±0.73, respectively (norm 0–5.5 IU/l). After 6 months of treatment in the comparison group, the level of acid phosphatase remained almost unchanged and amounted to 6.79±0.24, which indicates the absence of dynamics in this group. In the main group 1, the level of acid phosphatase was 4.93±0.26, which is only 27.6 % less than the initial result. In the main group 2, the level of acid phosphatase was 2.43±0.18, which is 64.2 % less than the initial result. Conclusions. The use of complex therapy using calcium phosphate preparations with vitamin D3 and aminobisphosphonates lasting 6 months increases bone mineralization by 13.05 %. The use of complex therapy using calcium phosphate preparations with vitamin D3 and aminobisphosphonates lasting 6 months reduces the activity of acid phosphatase by 64.2 %. The proposed treatment complex helps to reduce the destruction of bone tissue and stimulates the restoration of mineralization of bone tissue and hard tissues of teeth. Key words: tooth mineralization, osteoporosis, estrogen dysfunction, Hounsfield index.